Arduino-Based Digital Distance Measuring Device Experiment in Tinkercad for Electronics Learning - Riskawati; Said, Sukmawati; Tasya, Nurul Amelyan; Sanusi, Dirgah Kaso; Nurnaifa, Ihfa Indira; Agustini, Sri; Setiawan, Trisno; Barumbun, Mardyanto (Kasuari: Physics Education Journal (KPEJ), 2025)
This research aims to design and simulate an automatic distance measuring system based on Arduino Uno, utilizing the HC-SR04 ultrasonic sensor and a 16x2 LCD. The system was simulated within the Tinkercad virtual environment, enabling students to explore electronic concepts without relying on physical hardware. The simulation results demonstrated that the system could measure object distances accurately within a range of 2 cm to 400 cm, displaying the results in real time on the LCD. Tinkercad provides flexibility for experimentation, allowing students to understand the integration of hardware and software, including digital data processing and microcontroller programming. The system’s versatile applications include robotics, automatic parking systems, and distance-based security solutions. Despite its effectiveness, the system has limitations, such as sensitivity to environmental conditions and a restricted measurement range. Additional calibration is recommended to improve accuracy. Overall, the system offers an efficient and interactive approach to electronics education, equipping students with practical experience and enhancing their digital literacy. This study contributes to advancing technology-driven educational methods suited to the demands of the digital age.